Serum Helicobacter pylori Specific Antibodies Among Children With Undernourishment: A Case Control Study (Bangladesh Journal of Microbiology, 2012)
Infection with Helicobacter pylori has been implicated in the development of acute and chronic gastritis, peptic  ulcer disease, non-ulcer dyspepsia, and gastric MALT (mucosa-associated lymphoid tissue) lymphoma and   extragastroduodenal disorders. H. pylori infection may lead to development of hypochlorhydria and subsequent  malnourishment. This study examined the affiliation between H. pylori infection and some sociodemographic and nutritional variables including breast feeding practice, poverty, and availability of safe drinking water. Three hundred children with age ranging from zero to twelve years were enrolled in the study. Their nutritional status was assessed following standard protocol. A precoded questionnaire was filled up for obtaining data. Serostatus of anti H. pylori antibody was determined by in-house ELISA using formalin fixed   H. pylori whole cell antigen. The cut-off value of the ELISA was further validated by Immunoblot technique. Among the 149 case (malnourished) children, 107 (72%) contained anti-H. pylori antibodies and among the   control (nonmalnourished) population (n=151), 91 (60%) possessed anti-H. pylori antibodies, with an overall seroprevalence of 66%. Malnourishment was found to be more widespread among female (56%) than male children (44%). Highly significant association (p = 0.000) was reported between poor socioeconomic status and development of malnourishment. The degree of severity of malnourishment increased inversely with   the practice of exclusive breast-feeding up to 5 months of age (p = 0.010). The odds ratio relating breastfeeding to malnourishment reflected 52% reduction in the risk of development of malnourishment among   breast-fed children. The use of unsafe drinking water was associated with 5.33 times higher odds of developing   malnourishment. Poverty reduction strategies associated with improvement of hygiene condition and   promotion of breast feeding can actively contribute to the improvement of the nutritional status of the children of Bangladesh. DOI: http://dx.doi.org/10.3329/bjm.v28i1.11805 Bangladesh J Microbiol, Volume 28, Number 1, June 2011, pp 25-31